2006
DOI: 10.1038/sj.emboj.7601126
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2 changes conformation to inhibit Bax oligomerization

Abstract: Bcl‐2 inhibits apoptosis by regulating the release of cytochrome c and other proteins from mitochondria. Oligomerization of Bax promotes cell death by permeabilizing the outer mitochondrial membrane. In transfected cells and isolated mitochondria, Bcl‐2, but not the inactive point mutants Bcl‐2‐G145A and Bcl‐2‐V159D, undergoes a conformation change in the mitochondrial membrane in response to apoptotic agonists such as tBid and Bax. A mutant Bcl‐2 with two cysteines introduced at positions predicted to result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
203
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 234 publications
(221 citation statements)
references
References 25 publications
16
203
1
1
Order By: Relevance
“…Therefore, Bax dimers and oligomers could facilitate lateral sorting in the OMM or the formation of Bcl-2 protein-containing complexes (52). TMD-TMD interactions are consistent with models of Bax activation, suggesting separation of helices α5 and α6 (27,53) and the concerted insertion of both helices into the OMM (51,54). Conversely, Bax activation according to the clamp model would require a sequential mechanism to allow formation of antiparallel TMD interactions (28).…”
Section: Resultsmentioning
confidence: 76%
“…Therefore, Bax dimers and oligomers could facilitate lateral sorting in the OMM or the formation of Bcl-2 protein-containing complexes (52). TMD-TMD interactions are consistent with models of Bax activation, suggesting separation of helices α5 and α6 (27,53) and the concerted insertion of both helices into the OMM (51,54). Conversely, Bax activation according to the clamp model would require a sequential mechanism to allow formation of antiparallel TMD interactions (28).…”
Section: Resultsmentioning
confidence: 76%
“…The small oligomeric Bcl-2 pore may function to maintain the normal permeability of the MOM as suggested previously (26,27). In fact, we found that the conformation-altered Bcl-2 was able to inhibit the extensive oligomerization and large pore formation of Bax in both model and native mitochondrial membranes, thereby preventing apoptosis (23,24). Therefore, although interaction with tBid changes Bcl-2 to an active Bax-like conformation, it fails to convert Bcl-2 to a proapoptotic protein.…”
supporting
confidence: 49%
“…Indeed, we have shown that Bcl-2 permeabilizes a model MOM after conformational alterations induced by truncated Bid (tBid) (23). However, the Bcl-2 pore is too small to release cytochrome c because the tBid-activated Bcl-2 only forms small oligomers in the membrane unlike the tBid-activated Bax, which forms large oligomers (24,25). The small oligomeric Bcl-2 pore may function to maintain the normal permeability of the MOM as suggested previously (26,27).…”
mentioning
confidence: 99%
“…It was recently shown that Bcl-2 interaction with the proapoptotic proteins (Bid or Bax in the study) induced a change in its conformation, responsible for a more complete insertion in the MOM [49].…”
Section: Bax Binding To the Proteinsmentioning
confidence: 82%
“…The stable engagement of BaxBH3 inside the groove would confirm Bax remodelling and enable the release of activated Bax after Bax displacement from the groove by an antagonist of the interaction. The study by Duglosz et al [49] provides an interesting insight to this hypothesis as they demonstrate that Bcl-2 inhibitory effect on Bax-induced mitochondrial permeabilization was dependent on a change in Bcl-2 conformation and insertion to the mitochondrial membrane through the Hα5-α6. Of note, a conserved sequence in the BH1 domain, at the N-terminal part of Hα5 (NWGR), was shown to determine the binding between Bcl-2 or Bcl-xl and BH3 domains [5].…”
Section: Disruption Of the Interactionmentioning
confidence: 99%